Digitalization in the regional context: the case of e-government services in Latvia - Muravska, Tatjana; Stacenko, Sergejs; Zeibote, Zane (Warsaw University, Centre for Europe, 2018)
This article examines problems of the digital trends in economies and societies from two perspectives: the extension of a digital economy to social dimensions, and the role of digital government services in regional cohesion perspectives in Latvia. This methodological approach could serve as a tool for integrating a number of main goals related to the digitalisation trends in the EU, that require support of societies as well as the improvement of social welfare at the regional and national levels. The contribution aims to offer insight into the concept of social investment and innovation as well as co-creation concept and the impact of digitalisation of public services on regional cohesion. The study observes these implications in relation to the need to expand and adapt the content and approach of the digital services implementation. The further digital development as a precondition for diminishing regional and well being divide, facilitating administrative processes for people and entrepreneurs, as well as e-services availability in Latvia is discussed. The article concluded that efficient decision-making related to social investment and innovation for improving social welfare at regional and national levels needs implementation of digitalised services in a wider scale as they inevitably become more important due to the increased digital competitiveness of countries.
Keywords: Research Subject Categories::SOCIAL SCIENCES; social investment and innovation; regional cohesion; digital government services; digital literacy